Effect of fracture fill on frequency- and angle-dependent velocities and attenuation in fractured porous rocks - Kong, L.; Gurevich, Boris; Zhang, Y. (2016)
© 2016 SEG.In fractured reservoirs, seismic wave velocity and amplitude depend on frequency and incidence angle. The frequency dependency is believed to be principally caused by the wave-induced flow of pore fluid at the mesoscopic scale. In recent years, two particular phenomena, partial saturation and soft fractures, have been identified as significant mechanisms of wave induced flow. However these phenomena are usually treated separately. Recently a unified model was proposed for a porous rock with a set of aligned fractures filled with arbitrary fluid. Existing models treat waves propagating perpendicular to the fractures. In this paper, we extend the model to all propagation angles by assuming that the flow direction is perpendicular to the layering plane and is independent of the loading direction. We first consider the limiting cases through poroelastic Backus averaging, and then we obtain the full stiffness tensor of the equivalent TI medium. The numerical results show that when the bulk modulus of the fracture-filling fluid is relatively large, the dispersion and attenuation of P-waves are mainly caused by soft fracturs. While the bulk modulus of fluid in fractures is much smaller than that of matrix pores, the attenuation due to the 'partial saturation' mechanism dominants.